Analisis Dampak Pandemi Covid-19 Terhadap Pembiayaan Mudharabah Di Indonesia - Yudha, Fauzan Hadi (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze how the COVID-19 pandemic has affected the Islamic banking industry, specifically the financial performance of Islamic banks, Mudharabah financing, and monetary instruments in Indonesia. This study uses secondary data taken from OJK and BPS from 2017-2022. The data was processed using the Paired Sample T-Test method to determine statistical differences before and during the pandemic and the Error Correction Model (ECM) to estimate the influence between the variables FDR, NPF, BOPO, BI rate, Inflation, and COVID-19 pandemic on Mudharabah Financing in the long and short term. The Difference Test results prove that there is a significant decrease in all variables before and during the COVID-19 pandemic. The ECM test results also analyze that in the long term, the variables FDR, NPF, BOPO, Inflation have a significant positive effect on Mudharabah financing, while the BI rate and COVID-19 Dummy have a significant negative effect on Mudharabah financing. Surprisingly, even though the ECM model is valid, none of the 6 variables used in this study have a significant effect on Mudharabah financing in the short term.